The Influence of Financial Literacy, Hedonistic Lifestyle, and Tri Nga Teachings on Student Financial Management - Raflan Diana Megong, Leonardina; Anita Chandra Putry, Nur (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how financial literacy, hedonistic lifestyle, and Tri Nga teachings affect student financial management. Using a quantitative design, data were collected from 140 students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa through purposive sampling and analyzed using multiple linear regression. The results show that all three variables have positive and significant effects on student financial management, with Tri Nga teachings as the dominant predictor. Collectively, the model explains 82.5% of the variance. These findings imply that financial capability, lifestyle awareness, and cultural values should be strengthened in student financial education. Keywords: Financial Literacy, Hedonistic Lifestyle, Tri Nga Teachings, Student Financial Management